SOSIALISASI PEMBIBITAN KAKAO BAGI GENERASI MUDA DI SALINGKA KAMPUS UNIVERSITAS ANDALAS - Obel Obel; Nugraha Ramadhan; Rachmad Hersi Martinsyah; Meisilva Erona Sitepu; Munzir Busniah (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Cocoa is one of Indonesia's flagship commodities that significantly contributes to the nation's economy. However, recently, the fame of cocoa has been declining due to various issues affecting its cultivation, from upstream to downstream. One of these issues is the use of low-quality cocoa seeds, adversely impacting long-term production. This condition affects the enthusiasm of the community in cocoa cultivation, leading to a decline in national cocoa production. Hence, there's a need for early anticipation by socializing cocoa planting to the younger generation, especially those around the University Andalas campus in Padang. The objective of this activity is to impart knowledge about cocoa plants and the cocoa planting process to the younger generation around the University Andalas to support sustainable cocoa farming. The event took place in Sungai Balang, Pauh Kota Padang. The method employed was structured socialization to the younger generation at the University Andalas Campus. The activity's outcomes were evaluated through questionnaires. The results indicated high enthusiasm among the participants, with 87% expressing high satisfaction with the conducted activities, and 93% hoping for the sustainability of these initiatives. These results demonstrate an increased understanding among the younger generation at the University Andalas about cocoa plants, cocoa planting, and the entrepreneurial spirit based on cocoa planting. It's hoped that this initiative continues, supported by mentoring and guidance.